1997
DOI: 10.1007/pl00009699
|View full text |Cite
|
Sign up to set email alerts
|

NaCl-induced changes of NAD(P) malic enzyme activities in Eucalyptus citriodora leaves

Abstract: AbstractmThree-month-old plants of Eucalyptus citriodora were grown in a greenhouse in a culture medium adjusted either to 50 or 100 mM NaCl. Sodium was rapidly absorbed by the plants and as early as 3 weeks after treatment, an increased Na + level was observed in shoots of 50 mM NaCl plants. At this stage of treatment, the growth of plants was not reduced but the malate metabolism was modified. The malate content decreased in leaves while the specific activities of NAD and NADP-malic enzymes increased. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Si treatment of salt-stressed plants has been found to result in accumulation of organic acids in several plant species: Arabidopsis thaliana [62], Oryza sativa [63], Eucalyptus [64] and canola plants [65]. In accordance with the current study, these studies suggest that Si induced accumulation of organic acids and has stress alleviation effects on salt stressed plants.…”
Section: Metabolic Reprogramming Of Sugars and Organic Acids In Si Treated Salt Stressed Tomato Plantssupporting
confidence: 90%
“…Si treatment of salt-stressed plants has been found to result in accumulation of organic acids in several plant species: Arabidopsis thaliana [62], Oryza sativa [63], Eucalyptus [64] and canola plants [65]. In accordance with the current study, these studies suggest that Si induced accumulation of organic acids and has stress alleviation effects on salt stressed plants.…”
Section: Metabolic Reprogramming Of Sugars and Organic Acids In Si Treated Salt Stressed Tomato Plantssupporting
confidence: 90%
“…2002). In Eucalyptus plants, the induction of ME by NaCl has been also described (Farias De Aragao et al . 1997).…”
Section: Discussionmentioning
confidence: 80%
“…Induction of ICDH and G6PDH has been reported in pea and pepper plants subjected to Cd stress (Romero-Puertas et al 1999;León et al 2002), and in Mesembryanthemum crystallinum plants by salt stress (Popova et al 2002). In Eucalyptus plants, the induction of ME by NaCl has been also described (Farias De Aragao et al 1997).…”
Section: Discussionmentioning
confidence: 95%
“…Numerous studies have shown that the exposure to NaCl stress inhibits nitrate uptake (Word et al 1986;Botella et al 1994;Khan and Srivastava 1998) and results in decreased nitrate content in plants tissues (Hu et Schmidhalter 1998). Nevertheless, results of some investigations showed that nitrate level in plants is not modified by NaCl treatment (Farias de Aragao et al 1997). Our observations are consistent with opinion of Kaiser and Huber (2001) that NR in plants growing in stress conditions can be under strong substrate limitation.…”
Section: Discussionmentioning
confidence: 99%